2020
DOI: 10.35848/1882-0786/ab9ba3
|View full text |Cite
|
Sign up to set email alerts
|

Self-focusing 3D lithography with varying refractive index polyethylene glycol diacrylate

Abstract: This work presents self-focusing 3D lithography based on the refractive index changes of polyethylene glycol diacrylate (PEGDA) during photopolymerization. Since the polymerization of PEGDA leads to an increase in the refractive index, the UV light rays in the PEGDA undergo a refraction effect during exposure, thus being focused and forming 3D photopolymerized structures. We demonstrate the potential of self-focusing 3D lithography by fabricating PEGDA microneedles and trapezoid-shaped microwells. Their struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Previous experimental studies , have shown that the refractive index of a UV-curable resin increases during polymerization. The influence of the varying resin refractive indices on the spatial and temporal DoC distributions of UV-curable systems was investigated using the P-FDTD framework.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous experimental studies , have shown that the refractive index of a UV-curable resin increases during polymerization. The influence of the varying resin refractive indices on the spatial and temporal DoC distributions of UV-curable systems was investigated using the P-FDTD framework.…”
Section: Resultsmentioning
confidence: 97%
“…This value is the refractive index of uncured PEGDA. However, it is essential to point out that the refractive index of PEGDA increases during polymerization . Such effects will be discussed in the later sections.…”
Section: Resultsmentioning
confidence: 99%
“…1b . 24 Fig. 1c shows a picture of cone-shaped MNs, fabricated on a flexible PET film, using photopolymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Takahashi et al reported the self-focusing effect in fabricating MNs by the reflection on the interface between the solidified and liquid prepolymer, and UV light rays diverged after reaching the critical point and converged again to form gourd-shaped MNs. 24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation